2021
DOI: 10.1007/s12011-021-02654-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Urinary Lead (Pb) and Essential Trace Elements in Autism Spectrum Disorder: a Case-Control Study Among Preschool Children in Malaysia

Abstract: Lead (Pb) is a heavy metal which is abundant in the environment and known to cause neurotoxicity in children even at minute concentration. However, the trace elements calcium (Ca), magnesium (Mg), zinc (Zn) and iron (Fe) are essential to children due to its protective effect on neurodevelopment. The primary objective of this study was to assess the role of Pb and trace elements in the development of autism spectrum disorder (ASD) among preschool children. A total of 81 ASD children and 74 typically developed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 129 publications
1
13
0
1
Order By: Relevance
“…Although to our knowledge, this study is the first that investigated possible interactive associations of GST genes ( GSTP1 , GSTM1 , and GSTT1 ) and ASD status in relation to BPbCs, our findings suggest associations of certain GST genotypes with significantly lower BPbCs in children with ASD than in TD controls that are in line with the literature, indicating a possible role of GST genes in detoxification of Pb [ 10 , 27 , 29 , 63 , 64 , 65 ] and/or their associations with ASD status [ 14 , 16 ]. For example, our findings show significant associations between the presence of at least one Val allele for the GSTP1 Ile105Val polymorphism and lower BPbCs in children with ASD than in TD controls, suggesting a possible role for the Val allele in detoxification of Pb.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although to our knowledge, this study is the first that investigated possible interactive associations of GST genes ( GSTP1 , GSTM1 , and GSTT1 ) and ASD status in relation to BPbCs, our findings suggest associations of certain GST genotypes with significantly lower BPbCs in children with ASD than in TD controls that are in line with the literature, indicating a possible role of GST genes in detoxification of Pb [ 10 , 27 , 29 , 63 , 64 , 65 ] and/or their associations with ASD status [ 14 , 16 ]. For example, our findings show significant associations between the presence of at least one Val allele for the GSTP1 Ile105Val polymorphism and lower BPbCs in children with ASD than in TD controls, suggesting a possible role for the Val allele in detoxification of Pb.…”
Section: Discussionsupporting
confidence: 89%
“…Another study, from Turkey, that compared 30 ASD cases and 20 TD control children (3–12 years old) reported a significantly lower urine Pb concentration in children with ASD than in unmatched TD children (mean (95% CI) for ASD = 1.19 μg/g creatinine (-0.79, 3.17) vs. TD = 4.63 μg/g creatinine (0.80, 8.46), p < 0.01) [ 13 ]. Similarly, in a study from Malaysia, Wahil et al compared 81 ASD cases and 74 TD control children (3–6 years old) and reported significantly lower GM urinary Pb levels in ASD cases compared to unmatched TD controls (ASD mean (SD) = 0.26 μg/dL (0.31), TD mean (SD) = 0.58 μg/dL (0.41), p < 0.01) [ 16 ]. In another case–control study in Pakistan (age- and sex-matched), Rahbar et al compared 30 ASD cases and 30 TD controls (2–12 years old) and reported significantly lower GM BPbC in children with ASD compared to their age- and sex-matched TD controls (GM for ASD = 6.37 µg/dL vs. TD = GM 7.68 µg/dL, p = 0.05) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the risk of autism in association with other environmental pollutants (i.e., chemicals other than PAHs), and few studies have been conducted on the association between urinary PAHs metabolites and autism symptomology or risk. A recent study found a relationship between urinary lead, essential trace elements, and autism risk in children aged 3–6 years; the odds of ASD was also reduced statistically significantly, by 11.0% and 0.1% with increments of 1.0 μg/dl of urinary Zn and Pb, respectively (Abd Wahil et al, 2022). Another study found that urinary phthalate levels showed a statistically significant relationship with ASD risk (Jeddi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic factors partially underlie the etiology of ASD (Risch et al, 1999), current evidence demonstrates that single gene variations and chromosomal defects account for only approximately 10%–20% of incident ASD (Park et al, 2016; Schaefer et al, 2013). In addition, several studies have shown that environmental toxins, such as dioxins, dibenzofurans, bisphenol A, and phthalates, may be linked to the occurrence of ASD as well as to symptom phenotypes within ASD (Abd Wahil et al, 2022; Chehbani et al, 2020; Jeddi et al, 2016; Kim et al, 2018; Rahbar et al, 2017). This may be due to abnormal metabolism in those with ASD, or may instead represent an interesting finding that supports the hypothesis that exposure to these pollutants during prenatal development or early childhood may lead to or precipitate/aggravate ASD.…”
Section: Introductionmentioning
confidence: 99%